THE ROLE OF THE TEACHER’S PROFESSIONAL COMPETENCE IN CONFLICT SITUATIONS (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The article describes various theories of practical application of the knowledge, skills, and abilities of the teacher as a result of the professional activity of the teacher in the pedagogical activity, as a result of the professional activity of the teacher and the personal skills.